Potensi Belimbing Wuluh dan Jeruk Sitrun Sebagai Bahan Pengatur Ph pada Fermentasi Nata De Coco - Pariwanti Pariwanti (Faculty of Mathtmatics and Natural Sciences, 2006)
The effects of “belimbing wuluh” and citrun acid as pH conditioning in the Nata de coco fermentation was studied by using factorial experimental design. The objective af this research was to determine optimum addition oa natural citrate acids and its concentration at nata de coco fermentation. The treatments are kinds of natural citrate acids and its concentration in the three and four levels respectively. Kinds of natural citrate acids are sintatic citrate acid, ‘belimbing wuluh’ and citrum acid. Four levels concentration are 0,4%, 0,6%, 0,8% and 1,0%. The results showed that kinds of natural citrate acids and its concentration had sigbificant effect on thicness, throughput and pH but not for texture. The best fermentation process was obtained by using ‘belimbing wuluh’ at 0,4% concentrations.